Cellulose nanocrystal/calcium alginate-based porous microspheres for rapid hemostasis and wound healing. (1st October 2022) - Ouyang, Xiao-kun; Zhao, Lijuan; Jiang, Fangyuan; Ling, Junhong; Yang, Li-Ye; Wang, Nan
Abstract: Porous microsphere hemostatic materials, which possess rapid hemostatic, antibacterial, and wound healing-promotion properties, have key advantages over hemostatic dressings with a single hemostatic function. Using rod-shaped cellulose nanocrystals as the supporting framework, sodium alginate/cellulose nanocrystal porous microspheres (SA/CNC) were prepared using an inverse emulsion method. After SA/CNC self-assembly with the antibacterial polymer ε-polylysine, the hemostatic porous microspheres (PSLMs) showed high porosity, high liquid absorption capacity, and excellent coagulation properties. The in vitro and in vivo coagulation properties of PSLMs were evaluated and compared with those of the commercially available chitosan hemostatic powder. PSLMs had marked hemostatic effects in the following mouse hemorrhage models: caudal (81.20 s), liver (48.44 s), and femoral artery (71.66 s). After the introduction of ε-polylysine with excellent antibacterial properties to PSLMs, PSLMs effectively inhibited the activities of Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa . Graphical abstract: Unlabelled Image Highlights: Antibacterial, hemostatic, and healing-promoting porous microspheres were prepared. Porous microspheres showed excellent hemostatic properties in vitro and in vivo . Degradable porous microspheres have good in vivo and in vitro biocompatibility.